Visual Outcomes Following Diffractive-Refractive Multifocal Intraocular Lens Implantation : Literature Review - Yulinda Arty Laksmita; Tjahjono D Gondhowiardjo (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Purpose: To evaluate the result of diffractive-refractive multifocal intraocular lens (IOL) implantation, regarding the visual acuity, spectacle independency, and also related disturbing visual pnenomenon such as halo and glare. Methods: Seventeen articles collected from multiple sources including Pubmed, Clinical Key, and Ophthalmology Advance were reviewed. Visual acuity. Five types of diffractive-refractive multifocal IOL were found including ReSTOR SA60D3, SN60D3, SA6AD3, SA6DA1, and AT Lisa 809M. Uncorrected and corrected visual acuity, spectacle independency and undesired visual phenomenon data of each IOL were analyzed. Results: For binocular uncorrected distance and intermediate vision, ReSTOR SN6AD1 is better than other IOL. Meanwhile, in binocular uncorrected near visual acuity category, ReSTOR SA60D3 is superior. Highest percentage of patients reporting spectacle independency found in ReSTOR SA60D3 group. Halo was found in each IOL group, ranged from 32 to 65 percent patients. Glare was found in a smaller percentage, ranged from 25 to 61 percent patients. Conclusion: The best option for patients aiming for best visual acuity in distance to intermediate activity without spectacle use is ReSTOR SN6AD1. Meanwhile, the best option for patients aiming for best near visual acuity is ReSTOR SA60D3. Comprehensive preoperative education is crucial, considering the cost and benefit aspects of multifocal IOL implantation.